2017
DOI: 10.1007/s00737-017-0785-y
|View full text |Cite
|
Sign up to set email alerts
|

Mother–infant bonding in the postpartum period: assessment of the impact of pre-delivery factors in a clinical sample

Abstract: This study aims to examine the extent to which a variety of pre-delivery factors (demographic, reproductive, psychological, psychiatric, and psychopathological) predict disturbances in mother-infant bonding (MIB) in the postpartum period. Two hundred fifty-one pregnant women enrolled at a public perinatal psychiatric service were assessed between the first and second trimester of pregnancy and at 6-7 weeks after delivery. During pregnancy, the psychological risk factors were assessed with the Vulnerable Person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 85 publications
5
34
1
8
Order By: Relevance
“…In this study, the frequency of self-reported depressive and anxious mood in pregnancy were 5.0% and 11.8%, respectively, which are similar to the result of 11.3% for anxiety in pregnancy found in Ma's study [11] and the result of 4.5% for depression in pregnancy found in He's study [12], but lower than the result in Borja's study [13]. Literature review showed that there is a greater discrepancy in the reported prevalence of depression (from 3.5% to 29.0%) [14,15] and anxiety (from 9.1% to 59.5 %) [16,17] among the population of pregnant women.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the frequency of self-reported depressive and anxious mood in pregnancy were 5.0% and 11.8%, respectively, which are similar to the result of 11.3% for anxiety in pregnancy found in Ma's study [11] and the result of 4.5% for depression in pregnancy found in He's study [12], but lower than the result in Borja's study [13]. Literature review showed that there is a greater discrepancy in the reported prevalence of depression (from 3.5% to 29.0%) [14,15] and anxiety (from 9.1% to 59.5 %) [16,17] among the population of pregnant women.…”
Section: Discussionsupporting
confidence: 85%
“…Whereas the majority of previous studies did not distinguish between different types of maltreatment, the current study explored diverse forms, taking into account their co-occurrence. Thus far, Farré-Sender et al [27] have examined one single type of childhood maltreatment showing that maternal emotional abuse was a significant predictor of postpartum MIB impairment, which was not replicated in the current study. The analysis of only one type of childhood maltreatment could have led to an overestimation of its influence due to the common interrelations with other types of childhood maltreatment like emotional neglect [15].…”
Section: Discussioncontrasting
confidence: 83%
“…Furthermore, the variations of the study findings might be due to different study populations. Farré-Sender et al [27] conducted their study in a clinical population, whereas the current study was conducted in a general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore tested the association between manic symptoms and bonding in the PP group only. Analyses were adjusted for maternal age and primiparity [16,[37][38][39]. We report coefficients and their confidence intervals.…”
Section: Discussionmentioning
confidence: 99%